Preservation of Renal Allografts for Transplantation - Ayala-García, Marco Antonio; Hernández, Miguel Ángel Pantoja; Ramírez-Barba, Éctor Jaime; Encalada, Joel Máximo Soel; Yebra, Beatriz González (IntechOpen, 2012)
None